(untitled) (Research, Society and Development, 2021)
Coalho cheese is a popular product of the Northeastern culture, and the process of making it using raw milk is common, prior knowledge of the physical-chemical and centesimal composition of the food is relevant, both for influencing the healthy choice and for obtaining data from regarding what is being consumed with quality. The objective was to evaluate the physical-chemical characteristics and the chemical composition of rennet cheese marketed in cities in Ceará. Five different brands of rennet cheese (A, B, C, D and E) were collected in three replications, sent to the Pilot Plant for Milk and Derivatives of IFCE - Campus Limoeiro do Norte (CE). The samples were homogenized on a household grater, and stored under refrigeration (4 ± 2 ºC) until the time of analysis. Analyzes performed: physical-chemical (pH, water activity (Aw), titratable acidity and color), proximate composition (moisture, proteins, ash, lipids, total carbohydrates, and total caloric value). The statistical data by completely randomized design were subjected to analysis of variance (ANOVA) and Tukey’s test, through the program R Core Team, 2018, version 3.5.0, level of significance of 5%. Physical-chemical analyzes of rennet cheeses showed variability between samples, associated with production conditions, variation in the temperature of storage and commercialization of cheeses. The chemical composition and the caloric value expressed in Kcal varied between the samples studied, with the moisture content in accordance with what the legislation recommends for rennet cheese and the lipid values below the minimum required by the legislation.